Effect of the length of the microcycle on the daily external load, fatigue, sleep quality, stress, and muscle soreness of professional soccer players: A full-season study - Lozano, J. M. O.; Muyor, J. M., Pérez-Guerra, A.; Gómez, D.; Garcia-Unanue, J.; Sanchez-Sanchez, J.; Felipe, J. L. (Sports Health: A Multidisciplinary Approach, 2023)
Background: The aim of this study was to analyze the effect of the length of the microcycle (ie, training period from the day after the match to the following match) on the daily external load and perceived wellness of professional soccer players (Spanish LaLiga Smartbank).